VIDEOGAME ANALYTICS, SURVEILLANCE CAPITALISM AND THE RETENTIONAL ECONOMY OF PLAY - Egliston, Ben (AoIR Selected Papers of Internet Research, 2019)
Data analytics tools are increasingly prevalent in videogames and are reliant on the surveillant capture and relay of user data. In this paper I present some conceptual work and preliminary analysis of the analytics tool ‘DotaPlus’ used in Dota 2. Through my analysis, I frame DotaPlus as a site of ‘surveillance capitalism’, using data derived from various modes of surveillance to generate potentials for commercially desirable gameplay experience.